Effect of Preexisting Asthma on the Risk of ICU Admission, Intubation, and Death from COVID-19: A Systematic Review and Meta-Analysis - Bhattarai, Abhinav; Dhakal, Garima; Shah, Sangam; Subedi, Aastha; Sah, Sanjit Kumar; Mishra, Shyam Kumar (Interdisciplinary Perspectives on Infectious Diseases, 2022)
Background. The Centers for Disease Control and Prevention (CDC) identifies asthma as a comorbidity in COVID-19 that increases the risk of severity and death. However, research has shown that asthma is not associated with increased severity and death, thus making the consequences of asthma in COVID-19 unclear. Methods. We searched the electronic databases PubMed, WHO COVID-19 database, and Taylor and Francis Online for studies that compared the medical outcomes of COVID-19 between patients with and without asthma, from the emergence of SARS-CoV-2 in December 2019 to the 3rd of September 2021, excluded duplicates, reviews, editorials, and case reports, and screened the titles, abstracts, and full texts. The quality of the included studies was assessed using the Newcastle–Ottawa Scale (NOS) for nonrandomized studies. Rates of intensive care unit (ICU) admission, intubation, and death among patients with and without asthma were compiled and meta-analysis was conducted using a random-effects model. Results. Nineteen studies with a total of 289,449 participants met the inclusion criteria. COVID-19 patients with asthma had no significant association with increased risk of ICU admission, intubation, and death as compared with those without asthma ((odds ratio (OR) = 1.25, confidence interval (CI) = 0.90–1.74, I2 = 82%, X2 = 55.13, p<0.01), (OR = 0.89, CI = 0.59–1.34, I2 = 91%, X2 = 110.82, p<0.01), and (OR = 0.90, 95% CI = 0.63–1.27, I2 = 88%, X2 = 146.96, p<0.01)), respectively. Conclusion. Preexisting asthma did not significantly increase the risk of poorer prognosis and death from COVID-19.